Pengaruh Diabetes Melitus Terhadap Ketajaman Penglihatan Penyakit Katarak - An Nisa U Nur Hamidah; Putri Aulia Kusuma Ningrum; Sri Wahyuni; Zahra Amelia; Liss Dyah Dewi A (STIKes Ibnu Sina Ajibarang, 2024)
Cataract is an eye disease characterized by clouding of the lens of the eye so that it can interfere with vision. Cataracts are responsible for at least 50% of blindness cases worldwide. As life expectancy increases, the number of people affected by it also increases. Cataracts can be caused by endogenous and exogenous factors. In addition to cataracts, diseases that attack the retina can also cause vision loss. Diabetes is a disease that attacks the retina. Residents of the Copan Health Center area have low socioeconomic status and low education levels. The aim of this study was to investigate the impact of diabetes on vision. The study was conducted from April to May 2018 at the Puskesmas Kopan Central Lombok. The study design was cross-sectional with a sample of 73 respondents aged 40 years and over selected using simple random sampling. Visual acuity was measured by Tumbling E, random blood glucose measurement (≥ 200 mg/dl) was performed with Accu Check Active to determine diabetes, and data was analyzed with the Mann-Whitney test using SPSS version 16.0. Decide on a program with a confidence level of 95% (α = 0.05). Based on the results of statistical analysis, diabetes has a significant influence (42.5%).